THE EFFECT OF COFFEE PULP BOKASHI AND LOCAL MICROORGANISMS OF STALE RICE ON THE GROWTH OF ARABICA COFFEE (COFFEA ARABICA L) SEEDLINGS - Aris Tanan; Abdias Tandy Arrang (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
This study aims to determine the effect of coffee pulp bokashi and stale rice local microorganisms on the growth of Arabica coffee plant seedlings. This study used a factorial experiment, which tested two factors; namely bokashi coffee fruit skin in 5 dose levels, each: without treatment, 100 g/plant, 200 g/plant; 300 g/plant, and 400 g/plant; and local microorganisms of stale rice in 3 concentration levels, respectively: without treatment; 100 ml/L water; and 200 ml/L of water. The study results concluded that: Bokashi of coffee fruit skin at a dose of 400 g/plant had a good effect on plant height, the number of leaves, stem diameter, leaf area, root volume, plant dry weight, and net assimilation rate on arabica coffee plant seeds. Local microorganisms of stale rice with a concentration of 200 ml /L of water have a good effect on plant height, stem diameter, leaf area, number of leaves, plant dry weight, and net assimilation rate on arabica coffee seedlings. There was no interaction between the coffee fruit skin bokashi and stale rice local microorganisms on the coffee plant seeds.